Gallo-Romance imperfects betwixt multiple morphomic patterns. (November 2021) - Esher, Louise
Abstract : What kind of object is 'left behind' when part of an established paradigmatic distribution pattern splits away as a positively identifiable morphome? Drawing on comparative data from modern Occitan, French and Catalan, this study explores the wide range of paradigmatic distributions involving imperfect indicative forms (the 'remnants' of the erstwhile Latin infectum distribution, following the differentiation of the N- and L-pattern cells). While robust relationships are found to exist amongst imperfect indicative forms, there is little consistency in relationships between imperfect indicative forms and other paradigm cells, including other infectum reflexes. Furthermore, there is scant evidence for the modern distributions acting as productive templates for analogy. The study identifies distinctive lexical type frequency as a salient factor underlying observed contrasts in behaviour between individual distributions of inflectional exponents; and offers a means of reconciling the theoretical claim that all paradigmatic distributions are morphomic with the empirical observation that not all paradigmatic distributions are equally productive or resilient.